The Influence of Work Motivation and Work Discipline on the Performance of Employees of PT. Penjaminan Kredit Daerah Kalimantan Selatan - Kadir, Abdul; Malik, Abdul; Jayen, Fredy; Sutrisno, Sutrisno; Naimah, Naimah (Universitas Hang Tuah, 2024)
This research aims to determine and analyze the simultaneous and partial influence of work motivation and work discipline on employee performance at PT Penjaminan Kredit Daerah Kalimantan Selatan. This type of research uses descriptive quantitative with a survey approach where questionnaires will be distributed to all research respondents, where the population in this research is employees of PT Penjaminan Kredit Daerah Kalimantan Selatan, numbering . 36 were used as samples. Data collection techniques use questionnaires and interviews. The measurement scale uses a Likert scale with a preference level of 1 to 5. Data analysis uses multiple linear regression analysis. The test results show that work motivation and work discipline have a significant effect simultaneously and partially on employee performance at PT Penjaminan Kredit Daerah Kalimantan Selatan. Work motivation is a variable that has a dominant influence on employee performance at PT Penjaminan Kredit Daerah Kalimantan Selatan. The work environment has a dominant influence on the performance of Balangan Regency Library and Archives Service employees.